2010
DOI: 10.1073/pnas.1007866107
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation activates the transcriptional activity of Pax-6, an important transcription factor for eye and brain development

Abstract: Pax-6 is an evolutionarily conserved transcription factor regulating brain and eye development. Four Pax-6 isoforms have been reported previously. Although the longer Pax-6 isoforms (p46 and p48) bear two DNA-binding domains, the paired domain (PD) and the homeodomain (HD), the shorter Pax-6 isoform p32 contains only the HD for DNA binding. Although a third domain, the proline-, serineand threonine-enriched activation (PST) domain, in the C termini of all Pax-6 isoforms mediates their transcriptional modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 32 publications
3
79
0
1
Order By: Relevance
“…In contrast, during calcium-induced keratinocyte differentiation, overall enhanced SUMO1 modifications were accompanied by up-regulation of sumoylation system components (9). Although it is now well-established that sumoylation plays important roles in regulating cell differentiation (8)(9)(10)(11)(12), little is known regarding the impact of the individual SUMO paralogues. An early study has shown that haploinsufficiency of SUMO1 led to cleft lip and palate in embryonic mice (5), suggesting that SUMO2/3 do not substitute for SUMO1.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, during calcium-induced keratinocyte differentiation, overall enhanced SUMO1 modifications were accompanied by up-regulation of sumoylation system components (9). Although it is now well-established that sumoylation plays important roles in regulating cell differentiation (8)(9)(10)(11)(12), little is known regarding the impact of the individual SUMO paralogues. An early study has shown that haploinsufficiency of SUMO1 led to cleft lip and palate in embryonic mice (5), suggesting that SUMO2/3 do not substitute for SUMO1.…”
Section: Discussionmentioning
confidence: 93%
“…In ocular tissues, sumoylation helps to determine the differentiation of cone versus rod photoreceptors (11). Our recent study revealed that SUMO1-mediated sumoylation is an indispensable step toward activation of p32 Pax-6, a master regulator of eye and brain development (12). Although the effects of sumoylation on individual targets in regulating cell differentiation and other biological processes are being unraveled, it remains largely unknown how SUMO isoforms regulate cell differentiation and whether SUMO1 and SUMO2/3 display distinct functions.…”
mentioning
confidence: 99%
“…This phosphorylation enhances the transcriptional activities of PAX family proteins. In addition, PAX6 phosphorylation by homeodomain-interacting protein kinase 2 (31), sumoylation of PAX6 (32), and acetylation of PAX5 by p300 (33) are reported to be posttranslational modifications of PAX family proteins, and all enhance the transactivation of PAX family proteins; therefore, negative regulation of PAX5 function by phosphorylation seems to be unique. Serines of PAX5 phosphorylation sites are not conserved in any other PAX family proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A number of transcription factors are regulated by SUMO modification. SUMOdependent transcriptional stimulation has been reported for GATA4, PAX6, and the glucocorticoid receptor (13)(14)(15). However, SUMO modification more frequently results in transcriptional repression, as is the case for c-Jun, C/EBP family members, Sp3, IB␣, KAP-1, PPAR␥, and a number of other transcription factors (16 -19).…”
Section: Dna Replication-related Element Binding Factor (Dref)mentioning
confidence: 99%